Diseño de un protocolo para el análisis de requerimientos funcionales en la fabricación de prótesis de pierna BK (BELOW THE KNEE) (2020)
In this project a protocol will be designed to validate the BK prostheses (below the knee by its initials in English) carried out at the company Prosthetics Laboratories Inc. When delivering a BK leg prosthesis there are certain discomforts that the patient presents, so that certain adjustments must be made to it. This delays the delivery and validation of the prosthesis by the user. The objective of this project is that these delivery times of the prostheses decrease, as well as the patient's compliance. For this, a study can be made of the number of times this occurs, which adjustments are most required in these cases and thus establish a registry to follow with which a user-approved BK prosthesis is obtained in the first test of the same